Exploring a Positive Discipline Approach to Foster Academic Motivation in Senior High School: A Stakeholder Perspective - Hermahayu Hermahayu; Rasidi Rasidi; Aning Az Zahra (Bulletin of Counseling and Psychotherapy, 2025)
This study explores the perceptions of educators, students, and parents regarding the implementation of positive discipline in schools and its influence on students’ academic motivation. It examines how principals, teachers, students, supervisors, and parents understand and apply positive discipline, including its various forms, perceived effectiveness, challenges, and supporting factors. Data were gathered through Focus Group Discussions (FGDs) with 30 participants divided into four stakeholder-based groups. Using thematic analysis, the findings reveal that teachers’ understanding of positive discipline remains inconsistent, affecting the quality and uniformity of its implementation. While positive reinforcement and reflective group discussions are commonly practiced, punitive approaches still appear in some classrooms. The study shows that positive discipline contributes to increased student motivation, stronger classroom engagement, and healthier relationships within the school environment. Challenges include limited teacher training, inconsistent application, and occasional resistance from students or parents, whereas supportive school policies and strong communication with families serve as enabling factors. The study acknowledges several limitations, including a relatively small and heterogeneous participant group and the reliance on FGDs, which may introduce social desirability bias. Additionally, because the research focuses on senior high and vocational schools, its findings may not fully represent other educational levels. Despite these limitations, the study underscores the need for institutional support, ongoing teacher professional development, and active parental involvement to enhance the practice of positive discipline. It provides a culturally grounded perspective on positive discipline in Indonesian schools and highlights its role in fostering student motivation and cultivating a positive educational climate.